Hazards and Risks Investigation of the Fit Out Project of RMM Construc-tion: Basis for Creation of an Occupational Construction and Health and Safety Program - Masanga, Luisito P.; Gutierrez, Ernell Bautista; De Vera, Rommel (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The existence of hazards and risks in businesses is inevitable, specifically, in the construction industry. The research is qualitative by nature which aimed the identification and investigation of the actual hazards and risks in the workplace as experienced by the select construction workers as main participants in the research. A total of eleven (11) constructions workers were utilized in the research and selected by way of purposive sampling. During the focus discussions, participants are divided into three groups. Among others, results revealed the following construction-related hazards: Scattered Broken Tiles, Unstable Scaffolding, Scattered Nails, Insufficient Lightning, Exposed Extension Wire and Chiselling and Grinding, No Insulation and Physical Transport of Heavy materials. The research further investigated the level of risks in the identified hazard using the probability and severity matrix. At average, the identified risks obtained a high level of probability while severity at average is to medium or moderate only. Occupational Construction and Health and Safety Program was developed based on the results of this research.